Study on the policy literacy of the Republic of Korea regarding nuclear and new-renewable energy - Im, Eunok; Kim, Ju Kyong; Woo, Seung Min (Nuclear engineering and technology, 2022)
Policy literacy plays a critical role in enhancing deliberative communication among the public, policymakers, and experts. It also helps develop a positive view of policy by the public, which facilitates public acceptance. Despite its importance, however, policy literacy has received little attention in energy policy practice. Therefore, this study explores factors affecting the public's understanding and knowledge (i.e., policy literacy) of nuclear and new-renewable energy policies. Accordingly, we analyzed data from an online survey of 790 laypeople in Korea. Specifically, we examined the effects of trust, transparency, and policy public relations (PR) on the policy literacy of the public regarding the two alternative energy sources. The analysis revealed that people showed higher policy literacy about the alternative sources when provided with more transparent information and exposed to more policy PR activities. However, we found that trust in energy plant operators played a negligible role in improving policy literacy for both energy sources. Based on these findings, we developed some policy suggestions to secure the energy policy literacy of the public.